Superior supercapacitive performance of Cu2MnSnS4 asymmetric devices. Issue 2 (22nd December 2020) - Isacfranklin, M.; Yuvakkumar, R.; Ravi, G.; Velauthapillai, Dhayalan; Pannipara, Mehboobali; Al-Sehemi, Abdullah G.
Abstract : Renewable energy sources are considered the cornerstone of achieving a sustainable future for today's modern world. Abstract : Renewable energy sources are considered the cornerstone of achieving a sustainable future for today's modern world. In the current research on energy storage devices, transition metal sulfides are being explored as an excellent electrode material. In this study, the electrochemical performance of Cu2 MnSnS4 and its micro/nano-structural changes due to variations in the structure directing agents used in its fabrication were investigated. Synthesis of the sulfide sediments was confirmed via standard characterization techniques. The charge-storage electrochemical activity was explored via electrochemical characterization techniques. Furthermore, the electrochemical charge-storage behavior was enhanced by Cu2 MnSnS4 . The best cyclic stabilities obtained were 83%, 87%, and 89% of capacitive retention over 5000 cycles for AA, CA, and OA electrodes in three-electrode arrangements, respectively, while an 80.35% capacitance retention and 97.54% coulombic efficiency were achieved after 21 000 cycles in a fabricated device. The as-fabricated device exhibited an energy density of 27 W h kg −1 and power density of 759 W kg −1 at a current density of 1 A g −1 in the two-electrode setup.